2023
DOI: 10.1155/2023/1168262
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Application for Common Carp (Cyprinus carpio): I. Effects on Growth Performance, Humoral Immunity, Antioxidant Status, Immune-Related Genes, and Resistance against Heat Stress

Abstract: This study was done to evaluate the effect of different quercetin levels on growth performance, immune responses, antioxidant status, serum biochemical factors, and high-temperature stress responses in common carp (Cyprinus carpio). A total number of 216 common carp with an average weight of 27.21 ± 53  g were divided into 12 tanks ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 51 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…•− and catalyze it to H 2 O 2 and the dioxygen molecules [46]. Subsequently, H 2 O 2 is catalyzed by CAT and GPx [49]. In this study, dietary AE supplementation increased activities of CAT and GPx in the hepatopancreas and intestine, indicates that dietary AE improved fish antioxidant capacity.…”
Section: Dietary Ae Inclusion Enhanced Fish Growthsupporting
confidence: 57%
“…•− and catalyze it to H 2 O 2 and the dioxygen molecules [46]. Subsequently, H 2 O 2 is catalyzed by CAT and GPx [49]. In this study, dietary AE supplementation increased activities of CAT and GPx in the hepatopancreas and intestine, indicates that dietary AE improved fish antioxidant capacity.…”
Section: Dietary Ae Inclusion Enhanced Fish Growthsupporting
confidence: 57%
“…Some studies in zebrafish embryos found that acute extreme temperature treatment, whether low or high temperature, resulted in reduced aerobic performance and thermal sensitivity and a switch in muscle fibre type [16,17]. In a breeding trial with a heat stressor, it was found that the growth performance of Cyprinus carpio was significantly reduced after 60 days [18]. Cyprznus carpzo L. had the smoothest heart rate and metabolic frequency at 19.0 • C and, in the rest of the temperature conditions, both warming and cooling, sharp changes in heart rate and metabolic frequency were exhibited [19].…”
Section: Introductionmentioning
confidence: 99%